Aneuploidies level in sperm nuclei in patients with infertility. (6th June 2016) - Alchinbayev, Mirzakarim Karimovich; Aralbayeva, Araylyim Nugmanovna; Tuleyeva, Lazzat Namatullaevna; Duysenbayeva, Svetlana Melsovna; Makazhanov, Marat Abzalovich
Abstract : Male infertility is a relevant social and medical problem. Male infertility is mostly caused by genetic disorders. The purpose of the study was to analyze the correlation of chromosome aberrations, as well as DNA fragmentation and various manifestations of spermatogenesis disorder. Sperm samples of 58 males with infertility and 23 conditionally healthy males were studied. All patients diagnosed with asthenozoospermia, teratozoospermia, oligoasthenozoospermia and oligoteratozoospermia underwent subsequent analysis of sperm DNA fragmentation. Sperm DNA fragmentation was examined with sperm chromatin dispersion test (sperm chromatin dispersion, Spermprocessor, India) with an Axioscope 40 fluorescent microscope. Fluorescence in situ hybridization with fluorescent probes (Vysis Multi Vysion PGT, Abbot Molecular) was used to study chromosome abnormalities in sperm nuclei with regard to X and Y chromosomes, as well as to chromosomes 18 and 21. It was found that the development of pathospermia was characterized by genetic discontinuity, which manifests as DNA fragmentation and disjunction of chromosomes in meiosis with spermatogenesis. It was also found that the prevailing type of pathospermia in men with infertility was oligozoospermia. In addition, this group also had the highest rate of numerical chromosome abnormalities. This was caused by the degeneration of spermatozoids with aneuploidies in chromosomes.